2011
DOI: 10.1186/1471-2164-12-85
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of pepper and tomato reveals euchromatin expansion of pepper genome caused by differential accumulation of Ty3/Gypsy-like elements

Abstract: BackgroundAmong the Solanaceae plants, the pepper genome is three times larger than that of tomato. Although the gene repertoire and gene order of both species are well conserved, the cause of the genome-size difference is not known. To determine the causes for the expansion of pepper euchromatic regions, we compared the pepper genome to that of tomato.ResultsFor sequence-level analysis, we generated 35.6 Mb of pepper genomic sequences from euchromatin enriched 1,245 pepper BAC clones. The comparative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 47 publications
5
40
0
2
Order By: Relevance
“…(Suoniemi et al, 1996;Vicient et al, 1999), wheat (Charles et al, 2008;Salina et al, 2011) and pepper (Park et al, 2011(Park et al, , 2012b, have reported that the genomes expanded and were rearranged by accumulation of LTR-RTs. Our results suggest that LTR-RTs are also the main players in the enlargement and evolution of the ginseng genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Suoniemi et al, 1996;Vicient et al, 1999), wheat (Charles et al, 2008;Salina et al, 2011) and pepper (Park et al, 2011(Park et al, , 2012b, have reported that the genomes expanded and were rearranged by accumulation of LTR-RTs. Our results suggest that LTR-RTs are also the main players in the enlargement and evolution of the ginseng genome.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of LTR-RTs around genic regions has been reported in maize (SanMiguel et al, 1998;Kronmiller and Wise, 2009), wheat (Wicker et al, 2001;Salina et al, 2011), barley (Wicker et al, 2005) and pepper (Park et al, 2011(Park et al, , 2012b. In the pepper genome, accumulation of the Ty3/Gypsy elements such as Tat and Athila-like subgroups has resulted in expansion of euchromatic regions by random insertion (Park et al, 2011), while the Del-like subgroup has accumulated in constitutive heterochromatic regions such as pericentromeric regions (Park et al, 2012b). By contrast, the Del-like elements and their solo LTRs were found in the areas adjacent to the genic region of 5J07 (Figure 1c).…”
Section: Pgdel and Remodeling Of Euchromatic Regions In The Ginseng Gmentioning
confidence: 96%
“…Another primary reason for limited applied and basic research in pepper has been lack of a reference genome sequence of ∼3.3 Gb (11). Recent work comparing two members of the Solanaceae family (pepper and tomato) has begun to shed light on the processes that influence the dynamics of genome size in angiosperms (12,13).…”
Section: Significancementioning
confidence: 99%
“…Table 1 sums up the results of the analysis. Five sequences (Z05-760, V17-320B, W06-520, V01-1000, and Q07-1100) revealed extensive similarity to at least eight pepper BAC clones that are rich in LTR/Gypsy-like retrotransposons as reported by Park et al (2011). The N16-800 sequence showed significant similarity to the cDNA pepper clone KS24.…”
Section: Resultsmentioning
confidence: 58%